SYNTHESIS ALKANOLAMIDE TETRAHIDROXY OCTADECANOATE COMPOUND FROM CANDLE NUT OIL - Daniel Daniel (Universitas Gadjah Mada, 2009)
Candle nut oil could be transesterificated by methanol with concentrated H2SO4 as a catalyst to form fatty acid methyl esther. Methyl linoleate could be separated by Column Chromatography mechanism technic partition from fatty acid methyl ester (FAME) mixture, then it was treated by ethanolamine at base condition in benzene as solvent and sodium methylate as a catalyst at reflux condition for 6 hours to form an alkanolamide. Alkanolamide could be epoxydized by tert-buthyl hydroperoxyde and peroxygenase as a catalyst and it was refluxed for 6 hours at 40 °C and nitrogen gas condition to form the epoxy alkanolamide octadecanoate, and then it was hydrolyzed by HCl 0.1 M to form alkanolamide tetrahidroxy octadecanoate (Polyol). Alkanolamide tetrahidroxy octadecanoate could be separated by Column Chromatography using silica gel H 40 and the eluent was the mixture of chloroform, ethyl acetate, formic acid in a ratio 90:10:1 (v/v/v/). Determination of HLB value from alknolamide tetrahydroxy octadecanoate is 13.096. Therefore, this compound was particularly suitable for application as an o/w emulsifiers. All af the reaction steps were confirmed by using FT-IR, 1H-NMR, GC-MS, Gas Chromatography and TLC.